Intellectuals and Politics. - Brym, Robert (Routledge revivals., 2010)
An essay that analyses the relationship between intellectuals' social locations and their political orientations. It provides a discussion of the various sociological views of intellectuals and specifies some of the social conditions which encourage intellectuals to follow various directions on the political compass.